Soil-Water Characteristic Curve of Residual Soil from a Flysch Rock Mass - Josip Peranić; Željko Arbanas; Sabatino Cuomo; Matej Maček (Geofluids)
Depending on the nature of the material and suction range, laboratory measurements of the soil-water characteristic curve (SWCC) can be time-consuming and expensive, especially for residual soils, in which a wide range of particle sizes and soil structures typically results in SWCCs that cover a wide range of suction. Investigations of the SWCCs of residual soil from flysch rock masses are rare, and so far, no results were presented in the literature which were obtained by performing measurements on undisturbed specimens. In this paper, a detailed examination of water retention characteristics is performed for a specific type of residual soil (CL) formed by the weathering of a flysch rock mass. Measurements performed by using different techniques and devices on intact specimens were successfully combined to obtain the SWCC during both drying and wetting processes, under different stress conditions, and from saturated to air-dried conditions. Used procedures are suitable for the determination of SWCCs of soils that undergo volume changes during the drying or the wetting process, since instantaneous volumetric water content can be determined. Results presented in this paper can be used to assess the influence of desaturation of the residual soil covering flysch slopes during dry summer periods by providing key-in material properties required to analyze the transient rainfall infiltration process.